K probleme razrabotki realizatsii sportivno-ozdorovitel'noi programmy "prezidentskie sostyazaniya" - Mochenov, V. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
Explanation of the elaboration and realization of the sports-health-improvement programme "President's competition which has been established in Russia in 1997 to improve health status of the people, esp. children and youth and this way to create a better basis for sports.